Jordanian legislations about medicine protection, a foundational jurisprudential study - ElManaseer, Feras Hammoud; Al-rifai, Rudaina Ibrahim (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study examines Jordanian legislation related to pharmaceutical protection, focusing on laws governing drug monopolies, quality assurance, and regulatory oversight within the framework of Islamic jurisprudence. The researcher adopts an inductive approach by tracing the legal provisions concerned with pharmaceutical protection, particularly those embedded in consumer protection laws that regulate the production, distribution, and consumption of pharmaceuticals. These laws are then analyzed in light of Islamic legal principles and jurisprudential foundations. Methods: The study employs both descriptive and analytical methodologies. The descriptive method is used to comprehensively outline the legal framework surrounding pharmaceutical protection, while the analytical method is applied to critically examine relevant legislation in order to propose effective solutions for enhancing drug safety. This approach aims to mitigate the risks of fraud, counterfeiting, and manipulation that may occur throughout the drug’s lifecycle from production and storage to marketing and distribution. Results: The study finds that the protection of pharmaceuticals is primarily achieved through state-imposed regulations that ensure the safety and efficacy of drug products. These include requirements for pharmaceutical manufacturing companies, consumer protection measures, and laws aimed at preventing monopolistic practices within the pharmaceutical sector. Conclusions: The study concludes that such protections are grounded in Islamic jurisprudence, particularly in legal texts that prohibit monopolistic behavior and by analogy to the prohibition of food hoarding. This alignment underscores the ethical imperative of safeguarding public health.